I found you [compact disc, unabridged] : a novel - Jewell, Lisa (Dreamscape Media, LLC, 2017)
A lonely single mom who offers shelter to an amnesiac man and a young bride who is told that her missing husband never existed struggle to make sense of their transforming worlds and their connection to two teenagers whose lives were shattered by secrets two decades earlier.